Effectiveness of a city council’s environmental education module in enhancing pupils’ knowledge, attitude, behaviour intention and behaviour towards environment - Mohd Ismail, Kartini (2019)
Due to numerous environmental problems in Malaysia, education has been identified as one of the best methods to create the generation equipped with the knowledge, awareness, and strong implementation of sustainability. This study was undertaken in responsible to evaluate an instructional method of Environmental Education Module. This module had been used for more than 20 years as the main teaching and learning tool in Awareness Camp as one of the initiatives in informal education. One group pre and post-quasi-experimental study was conducted involves 32 primary five pupils from two identified school in the area under the supervision of MBPJ via purposive sampling. The sample undergoes the intervention for three days and two nights in a camp in Bagan Lalang. Four series of test were conducted namely pre-test (to access initial level of knowledge, attitude, behaviour intention and behaviour before intervention), post-test (to access immediate effects of intervention), one month post-delayed test (to access continuous effects of intervention) and six months post-delayed test (to access continuous and long term effects of intervention). Based on the analysis of Repeated Measure ANOVA it is found that there is a significant different in knowledge Wilks’ Lambda = .409, F (3, 29) = 13.951, p = .00 <0.005, eta2 = .591 and in behaviour intention Wilks’ Lambda = .60, F (3, 29) = 1.193, p = 0.002 < 0.005, eta2 = .04. Thus, hypothesis Ho1 and Ho3 were rejected. Further analysis by pairwise comparison, Post Hoc with Bonferroni adjustment found that there is a statistically difference found in knowledge in the pair of post-test (M = 15.53, SD = 2.94) compare to the pre-test (M = 11.50, SD = 3.50, one month post-delayed test (M = 15.28, SD = 2.79) compare to the pre-test (M = 11.50, SD = 3.50) and six months post-delayed test (M = 14.75, SD = 2.90) compare to the pre-test (M = 11.50, SD = 3.50). This indicates that the module able to give positive impacts to enhance pupils' knowledge towards the environment and persist it until six months upon completion of the intervention. On the other hand, a similar result was also found in behaviour intention in the pair of post-test (M = 4.12, SD = 0.31) when compared pre-test (M = 3.88, SD = 3.041). This indicates that the module able to trigger and enhance the behaviour intention towards the environment for a very short period of time. This suggested that the usage of the module as the main teaching and learning tool in Awareness Camp conducted by MBPJ capable of enhancing knowledge and behaviour intention. Perhaps, the cultivation of domains studied might be more efficient if the effort involves a long term and continuous initiatives with add on elements to enhance the module for further usage in the future.